Secondary teachers' geometrical figure apprehension: their ability to construct geometrical proof and to predict students' difficulties - Athanasios Gagatsis; Zoi Geitona; Rita Panaoura; Iliada Elia (Dipartimento formazione e apprendimento - Scuola universitaria professionale della Svizzera italiana; Repubblica e Canton Ticino - Dipartimento dell'educazione, della cultura e dello sport (DECS), 2023)
The present study investigates in-service secondary teachers' geometrical figure apprehension in relation to their ability to construct geometrical proofs and to predict didactically their students' difficulties and mistakes. The theoretical framework of analysis is based on Duval's geometrical figure apprehension which was taught to the teachers as part of an in-service training course in didactics of mathematics, offered by one of the researchers. As part of the course final assessment, a written test consisting of various geometrical tasks was constructed and administered to the sample. Participants' answers in both solving and interpreting difficulties related to the tasks were analyzed. The results of the study indicate that theories and concepts of didactics of geometry can shed light to various facets of teaching and learning of geometry. A teacher who presents a correct solution at a task does not necessarily identify or understand the possible difficulties faced by students. Discussion concentrates on teaching implications about geometry and geometrical proof.